Anti-ultraviolet aging coating for outer wall of pipeline and application of anti-ultraviolet aging coating
By applying a modified coating to the outer wall of the pipe, the problem of pipe aging under ultraviolet radiation is solved by using epoxy resin, additives, curing agents, nanocellulose modifiers and regulators. This achieves a coordinated balance of coating performance and UV resistance, and improves the pipe's impact resistance and adhesion.
Patent Information
- Application Number
- CN202510947413.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-11-18
AI Technical Summary
Existing pipe outer wall coatings are prone to aging under long-term exposure to ultraviolet radiation, leading to deterioration of material properties, poor adhesion and impact resistance, and insufficient UV stability, posing safety hazards.
A modified paint is applied to the outer wall of the pipe. The modified paint consists of epoxy resin, additives, curing agent, reinforcing agent and regulator based on nanocellulose modification. Through the combination of nanocellulose modifier and regulator, a coating with excellent impact resistance, adhesion and UV stability is formed.
It achieves a balanced performance of the coating, with excellent impact resistance and adhesion, significantly improved UV protection stability, extended pipeline service life, and reduced safety hazards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to anti-ultraviolet aging coatings for the outer walls of pipes and their applications. Background Technology
[0002] In various pipeline systems, especially those exposed to the outdoor environment for extended periods, such as urban gas pipelines, water supply and drainage pipelines, and chemical transport pipelines, aging problems caused by ultraviolet radiation are prevalent. Ultraviolet radiation can alter the molecular structure of the pipeline's outer wall material, gradually degrading its performance, leading to phenomena such as cracking, powdering, and reduced strength. This not only shortens the pipeline's service life but may also cause safety hazards such as leaks, resulting in economic losses and environmental pollution.
[0003] The coatings used on the outer walls of existing pipes have poor adhesion, and it is difficult to balance the impact resistance and adhesion of the products. In addition, the products have poor UV protection stability, which limits the efficiency of the products. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide an anti-ultraviolet aging coating for the outer wall of pipes and its application, so as to solve the problems mentioned in the background art.
[0005] The present invention solves the technical problem by adopting the following technical solution: This invention provides a UV-resistant aging-resistant coating for the outer wall of a pipe. The UV-resistant aging-resistant coating is formed by applying a modified paint to the outer wall of the pipe, with a coating thickness of 1-2 mm. The modified paint includes the following raw materials in parts by weight: 35-40 parts epoxy resin, 4-7 parts additives, 8-12 parts curing agent, and 30-35 parts acetone solvent. The modified coating also includes 8 to 12 parts of a reinforcing agent based on nanocellulose modification and 4 to 7 parts of a modifier.
[0006] Preferably, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming co-solvent prepared in a weight ratio of 3:1, wherein the defoamer is glycerol trihydroxy polyether; and the film-forming co-solvent is diethylene glycol butyl ether.
[0007] Preferably, the method for preparing the reinforcing agent based on nanocellulose modification is as follows: S1: Mix 3-5 parts of nanocellulose, 2-5 parts of carbon nanotubes and 1-2 parts of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 55-60℃ for 1 hour, and mix the preheated calcium sulfate whiskers, nano silica sol and ethanol solvent in a weight ratio of 3:1:5 to obtain whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1000-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0008] Preferably, the stirring temperature for the stirring process is 55-60℃, the stirring time is 1 hour, and the stirring speed is 450-500 r / min.
[0009] The reinforcing agent based on nanocellulose modification uses nanocellulose in combination with carbon nanotubes and other raw materials. It is further modified by a modifier composed of soybean protein, urea solution and ammonium persulfate, and calcium sulfate whiskers are preheated and mixed with nano-silica sol and other raw materials. Through the improvement of the combination of raw materials, the whisker liquid and the nanocellulose-based modifier are mutually improved. The resulting nanocellulose-based reinforcing agent optimizes the performance coordination and performance stability of the product in the system.
[0010] Preferably, the urea solution has a mass fraction of 2-5%.
[0011] Preferably, the method for preparing the regulator is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 350-400W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 4-7 parts of sodium lignosulfonate solution, 3-5 parts of boron nitride, 2-4 parts of basalt fiber and 1-2 parts of lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0012] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.
[0013] The nano-titanium oxide is improved by irradiating it and then combining it with a conditioning liquid made of sodium lignosulfonate solution, boron nitride, basalt fiber, and lanthanum oxide. Through the improved synergistic effect between the raw materials, the resulting conditioning agent has a better synergistic effect with the reinforcing agent based on nanocellulose modification, thereby further improving the performance of the product.
[0014] Preferably, the sodium lignosulfonate solution has a mass fraction of 5-8%.
[0015] The present invention also provides an application of an anti-ultraviolet aging coating on the outer wall of a pipe in a pipe.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The UV-resistant coating of this invention is made by blending epoxy resin, additives, curing agents, and reinforcing and regulating agents based on nanocellulose modification. The modified paint, made by the coordinated combination of raw materials, is applied to the outer wall of the pipe. The resulting coating product has excellent impact resistance and adhesion, with a balanced performance and significant UV resistance. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] The anti-UV aging coating on the outer wall of the pipe in this embodiment is formed by applying a modified paint to the outer wall of the pipe to form an anti-UV aging coating with a coating thickness of 1-2 mm. The modified paint includes the following raw materials in parts by weight: 35-40 parts epoxy resin, 4-7 parts additives, 8-12 parts curing agent and 30-35 parts acetone solvent. The modified coating also includes 8 to 12 parts of a reinforcing agent based on nanocellulose modification and 4 to 7 parts of a modifier.
[0019] In this embodiment, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:1. The defoamer is glycerol trihydroxy polyether; and the film-forming cosolvent is diethylene glycol butyl ether.
[0020] The preparation method of the reinforcing agent based on nanocellulose modification in this embodiment is as follows: S1: Mix 3-5 parts of nanocellulose, 2-5 parts of carbon nanotubes and 1-2 parts of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 55-60℃ for 1 hour, and mix the preheated calcium sulfate whiskers, nano silica sol and ethanol solvent in a weight ratio of 3:1:5 to obtain whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1000-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0021] In this embodiment, the stirring temperature is 55-60℃, the stirring time is 1 hour, and the stirring speed is 450-500 r / min.
[0022] The urea solution in this embodiment has a mass fraction of 2-5%.
[0023] The preparation method of the regulator in this embodiment is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 350-400W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 4-7 parts of sodium lignosulfonate solution, 3-5 parts of boron nitride, 2-4 parts of basalt fiber and 1-2 parts of lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0024] In this embodiment, the ultrasonic power for ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.
[0025] The sodium lignosulfonate solution in this embodiment has a mass fraction of 5-8%.
[0026] This embodiment describes the application of an anti-UV aging coating on the outer wall of a pipe in a pipe.
[0027] Example 1. The anti-UV aging coating on the outer wall of the pipe in this embodiment is formed by applying a modified paint to the outer wall of the pipe to form an anti-UV aging coating with a coating thickness of 1 mm. The modified paint includes the following raw materials in parts by weight: 35 parts epoxy resin, 4 parts additives, 8 parts curing agent and 30 parts acetone solvent. The modified coating also includes 8 parts of a reinforcing agent based on nanocellulose modification and 4 parts of a modifier.
[0028] In this embodiment, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:1. The defoamer is glycerol trihydroxy polyether; and the film-forming cosolvent is diethylene glycol butyl ether.
[0029] The preparation method of the reinforcing agent based on nanocellulose modification in this embodiment is as follows: S1: Mix 3 parts of nanocellulose, 2 parts of carbon nanotubes and 1 part of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 55°C for 1 hour, then mix the preheated calcium sulfate whiskers, nano-silica sol, and ethanol solvent in a weight ratio of 3:1:5 to obtain a whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1000 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0030] In this embodiment, the stirring temperature is 55℃, the stirring time is 1 hour, and the stirring speed is 450 r / min.
[0031] The urea solution in this embodiment has a mass fraction of 2%.
[0032] The preparation method of the regulator in this embodiment is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 350W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 4 parts sodium lignosulfonate solution, 3 parts boron nitride, 2 parts basalt fiber and 1 part lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0033] In this embodiment, the ultrasonic power for ultrasonic treatment is 350W, and the ultrasonic treatment lasts for 1 hour.
[0034] The sodium lignosulfonate solution in this embodiment has a mass fraction of 5%.
[0035] This embodiment describes the application of an anti-UV aging coating on the outer wall of a pipe in a pipe.
[0036] Example 2. The anti-UV aging coating on the outer wall of the pipe in this embodiment is formed by applying a modified paint to the outer wall of the pipe to form an anti-UV aging coating with a coating thickness of 2mm. The modified paint includes the following raw materials in parts by weight: 40 parts epoxy resin, 7 parts additives, 12 parts curing agent and 35 parts acetone solvent. The modified coating also includes 12 parts of a reinforcing agent based on nanocellulose modification and 7 parts of a modifier.
[0037] In this embodiment, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:1. The defoamer is glycerol trihydroxy polyether; and the film-forming cosolvent is diethylene glycol butyl ether.
[0038] The preparation method of the reinforcing agent based on nanocellulose modification in this embodiment is as follows: S1: Mix 5 parts of nanocellulose, 5 parts of carbon nanotubes and 2 parts of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 60°C for 1 hour, then mix the preheated calcium sulfate whiskers, nano-silica sol, and ethanol solvent in a weight ratio of 3:1:5 to obtain whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0039] In this embodiment, the stirring temperature is 60℃, the stirring time is 1 hour, and the stirring speed is 500 r / min.
[0040] The urea solution in this embodiment has a mass fraction of 5%.
[0041] The preparation method of the regulator in this embodiment is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 400W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 7 parts sodium lignosulfonate solution, 5 parts boron nitride, 4 parts basalt fiber and 2 parts lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0042] In this embodiment, the ultrasonic power for ultrasonic treatment is 400W, and the ultrasonic treatment lasts for 1 hour.
[0043] The sodium lignosulfonate solution in this embodiment has a mass fraction of 8%.
[0044] This embodiment describes the application of an anti-UV aging coating on the outer wall of a pipe in a pipe.
[0045] Example 3. The anti-UV aging coating on the outer wall of the pipe in this embodiment is formed by applying a modified paint to the outer wall of the pipe to form an anti-UV aging coating with a coating thickness of 1.5 mm. The modified paint includes the following raw materials in parts by weight: 37.5 parts epoxy resin, 5.5 parts additives, 10 parts curing agent and 30-35 parts acetone solvent. The modified coating also includes 10 parts of a reinforcing agent based on nanocellulose modification and 5.5 parts of a modifier.
[0046] In this embodiment, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:1. The defoamer is glycerol trihydroxy polyether; and the film-forming cosolvent is diethylene glycol butyl ether.
[0047] The preparation method of the reinforcing agent based on nanocellulose modification in this embodiment is as follows: S1: Mix 4 parts of nanocellulose, 3.5 parts of carbon nanotubes and 1.5 parts of silane coupling agent KH550 evenly to obtain a nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 57.5℃ for 1 hour, and mix the preheated calcium sulfate whiskers, nano-silica sol and ethanol solvent in a weight ratio of 3:1:5 to obtain whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1250 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0048] In this embodiment, the stirring temperature is 57°C, the stirring time is 1 hour, and the stirring speed is 470 r / min.
[0049] The urea solution in this embodiment has a mass fraction of 3.5%.
[0050] The preparation method of the regulator in this embodiment is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 375W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 5.5 parts sodium lignosulfonate solution, 4 parts boron nitride, 3 parts basalt fiber and 1.5 parts lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0051] In this embodiment, the ultrasonic power for ultrasonic treatment is 370W, and the ultrasonic treatment lasts for 1 hour.
[0052] The sodium lignosulfonate solution in this embodiment has a mass fraction of 6.5%.
[0053] This embodiment describes the application of an anti-UV aging coating on the outer wall of a pipe in a pipe.
[0054] Example 4. The anti-UV aging coating on the outer wall of the pipe in this embodiment is formed by applying a modified paint to the outer wall of the pipe to form an anti-UV aging coating with a coating thickness of 1 mm. The modified paint includes the following raw materials in parts by weight: 37 parts epoxy resin, 5 parts additives, 9 parts curing agent and 32 parts acetone solvent. The modified coating also includes 9 parts of a reinforcing agent based on nanocellulose modification and 5 parts of a modifier.
[0055] In this embodiment, the epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:1. The defoamer is glycerol trihydroxy polyether; and the film-forming cosolvent is diethylene glycol butyl ether.
[0056] The preparation method of the reinforcing agent based on nanocellulose modification in this embodiment is as follows: S1: Mix 4 parts of nanocellulose, 3 parts of carbon nanotubes and 1 part of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 56°C for 1 hour, then mix the preheated calcium sulfate whiskers, nano-silica sol, and ethanol solvent in a weight ratio of 3:1:5 to obtain a whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1200 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
[0057] In this embodiment, the stirring temperature was 57°C, the stirring time was 1 hour, and the stirring speed was 460 r / min.
[0058] The urea solution in this embodiment has a mass fraction of 3%.
[0059] The preparation method of the regulator in this embodiment is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 360W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 5 parts sodium lignosulfonate solution, 4 parts boron nitride, 3 parts basalt fiber and 1 part lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
[0060] In this embodiment, the ultrasonic power for ultrasonic treatment is 360W, and the ultrasonic treatment lasts for 1 hour.
[0061] The sodium lignosulfonate solution in this embodiment has a mass fraction of 6%.
[0062] This embodiment describes the application of an anti-UV aging coating on the outer wall of a pipe in a pipe.
[0063] Comparative Example 1. Unlike Example 3, no reinforcing agent based on nanocellulose modification was added.
[0064] Comparative Example 2. Unlike Example 3, whisker solution was not added in the preparation of the reinforcing agent based on nanocellulose modification.
[0065] Comparative Example 3. Unlike Example 3, no nanocellulose-based modifier was added in the preparation of the reinforcing agent based on nanocellulose modification.
[0066] Comparative Example 4. Unlike Example 3, this method does not involve the addition of nanocellulose and carbon nanotubes in the preparation of the nanocellulose modifier.
[0067] Comparative Example 5. Unlike Example 3, no regulator was added.
[0068] Comparative Example 6. The difference from Example 3 is that the preparation method of the conditioning liquid is different, and boron nitride and basalt fiber were not added.
[0069] Examples 1-4 and Comparative Examples 1-6 underwent conventional performance tests for impact resistance and adhesion. The test results are as follows:
[0070] As can be seen from Examples 1-4 and Comparative Examples 1-6, the product of the present invention can achieve a coordinated improvement in impact resistance and adhesion performance, while the product has excellent UV stability and can achieve long-term UV stability. The product's performance deteriorates significantly because neither a reinforcing agent based on nanocellulose modification nor a regulator is added. By combining and coordinating the two, the product's performance is significantly improved. In the preparation of reinforcing agents based on nanocellulose modification, whisker liquid was not added; in the preparation of reinforcing agents based on nanocellulose modification, nanocellulose modifiers were not added; in the preparation of nanocellulose modifiers, nanocellulose and carbon nanotubes were not added; and the preparation methods of conditioning liquids were different. Boron nitride and basalt fibers were not added, and the performance of the products tended to deteriorate. Only the raw materials obtained using the method of this invention showed the most significant performance effect. The preparation of the reinforcing agents and conditioning liquids based on nanocellulose modification of this invention is unique, and the specific method of this invention yields the best results.
[0071] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0072] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A UV-resistant coating for the outer wall of a pipe, characterized in that, The UV-resistant aging coating is formed by applying a modified paint to the outer wall of the pipe, with a coating thickness of 1-2 mm. The modified paint includes the following raw materials in parts by weight: 35-40 parts epoxy resin, 4-7 parts additives, 8-12 parts curing agent and 30-35 parts acetone solvent. The modified coating also includes 8 to 12 parts of a reinforcing agent based on nanocellulose modification and 4 to 7 parts of a modifier.
2. The anti-UV aging coating for the outer wall of the pipe according to claim 1, characterized in that, The epoxy resin is E51 epoxy resin; the curing agent is a fatty amine curing agent; the additives are defoamer and film-forming cosolvent, which are prepared in a weight ratio of 3:
1. The defoamer is glycerol trihydroxy polyether; the film-forming cosolvent is diethylene glycol butyl ether.
3. The anti-UV aging coating for the outer wall of the pipe according to claim 1, characterized in that, The preparation method of the reinforcing agent based on nanocellulose modification is as follows: S1: Mix 3-5 parts of nanocellulose, 2-5 parts of carbon nanotubes and 1-2 parts of silane coupling agent KH550 evenly to obtain nanocellulose composite agent; A modifier is obtained by mixing soybean protein, urea solution and ammonium persulfate in a weight ratio of 3:5:
1. A nanocellulose composite agent and the modifier are stirred in a weight ratio of 3:5 to obtain a nanocellulose-based modifier. S2: Preheat calcium sulfate whiskers at 55-60℃ for 1 hour, and mix the preheated calcium sulfate whiskers, nano silica sol and ethanol solvent in a weight ratio of 3:1:5 to obtain whisker solution. Whiskers and nanocellulose-based modifier were mixed at a weight ratio of 3:5 and ball-milled at a speed of 1000-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain the nanocellulose-based reinforcing agent.
4. The anti-UV aging coating for the outer wall of the pipe according to claim 3, characterized in that, The stirring temperature for the stirring process is 55-60℃, the stirring time is 1 hour, and the stirring speed is 450-500 r / min.
5. The anti-UV aging coating for the outer wall of the pipe according to claim 3, characterized in that, The mass fraction of the urea solution is 2-5%.
6. The anti-UV aging coating for the outer wall of the pipe according to claim 1, characterized in that, The method for preparing the regulator is as follows: S11: Irradiate nano-titanium oxide in a proton irradiation chamber for 1 hour at an irradiation power of 350-400W. After irradiation, irradiated nano-titanium oxide is obtained. S12: Mix 4-7 parts of sodium lignosulfonate solution, 3-5 parts of boron nitride, 2-4 parts of basalt fiber and 1-2 parts of lanthanum oxide evenly to obtain a conditioning solution; Irradiated nano-titanium oxide and conditioning solution were ultrasonically treated at a weight ratio of 4:
7. After ultrasonication, the mixture was filtered and dried to obtain the conditioning agent.
7. The anti-UV aging coating for the outer wall of the pipe according to claim 6, characterized in that, The ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic treatment lasts for 1 hour.
8. The anti-UV aging coating for the outer wall of the pipe according to claim 6, characterized in that, The sodium lignosulfonate solution has a mass fraction of 5-8%.
9. The application of the anti-UV aging coating on the outer wall of the pipeline as described in any one of claims 1-8 in the pipeline.